The effect of Snoezelen intervention on problem behaviors in children with cerebral palsy: A randomized controlled trial - Mina Kim; Sook-Hee Yi; Jee-Sun Lee; Ji-Young Lee; Yun-Tae Hwang; Jeong-Soo Kim (Complementary Therapies in Medicine)
Aim: To evaluate the effect of Snoezelen intervention on problem behaviors in children with cerebral palsy (CP) and to analyze its correlation with motor function, as measured by the Gross Motor Function Classification System (GMFCS). Method: This study is registered under the Clinical Research Information Service (CRIS) with the registration number KCT0002794. The unique protocol ID for this trial is SRH2018R-01. A randomized controlled trial with 28 children (aged 2–5 years) with CP was conducted. The experimental group received Snoezelen intervention three times a week for four weeks. Problem behaviors were assessed using the CBCL 1.5–5 and K-PSI, and motor function was assessed using the GMFCS. Results: The experimental group showed a significant reduction in emotionally reactive behavior (p = 0.044). A strong negative correlation (Spearman's ρ = −0.744, p = 0.002) was found between GMFCS scores and changes in emotionally reactive behavior. Interpretation: The Snoezelen intervention may reduce emotional reactivity and enhance emotional stability in children with CP, although its effectiveness may vary depending on the level of motor impairment. Further research is needed to confirm these findings.